2004
DOI: 10.1111/j.1439-0272.2004.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromatin integrity in human sperm using acridine orange staining with different fixatives and after cryopreservation

Abstract: Staining of cells with acridine orange (AO) has been widely accepted as a predictor of DNA damage in many cell types. Because of variability of protocols used in previous studies, the AO staining technique has not been widely accepted as a screening test to predict DNA damage in human sperm. In order to further validate the use of AO staining, sperm were evaluated using numerous variations in the staining protocol. This study also elucidated the effects of cryopreservation on sperm DNA. Sperm fixation in Carno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 22 publications
2
46
0
4
Order By: Relevance
“…Cryopreservation induces chromatin instability, DNA strand breaks and apoptosis in spermatozoa [4,5,24,25] and thereby reduces their functional competence. Poorly organized chromatin of spermatozoa from infertile men [26] increases their susceptibility to freeze-thaw-induced DNA damage compared to fertile men [27], which poses further challenge in semen cryopreservation technology.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation induces chromatin instability, DNA strand breaks and apoptosis in spermatozoa [4,5,24,25] and thereby reduces their functional competence. Poorly organized chromatin of spermatozoa from infertile men [26] increases their susceptibility to freeze-thaw-induced DNA damage compared to fertile men [27], which poses further challenge in semen cryopreservation technology.…”
Section: Discussionmentioning
confidence: 99%
“…The danger is that such spermatozoa are still able to fertilize the oocyte, however, the mutations and defects did not possible to discover until the embryo has divided and the fetus has developed (Twigg et al, 1998). At present exist the opinion that DNA decondensation or fragmentation may occur in different magnitudes, which will depend on the process or the kind of cryoprotectant used (Schuffner et al, 2001;Chohan et al, 2004;Ngamwuttiwong & Kunathikom, 2007;Yildiz et al, 2007). Unfortunately, until now this question is still open, because it is not entirely clear what the effect of cryopreservation on DNA integrity is, and what would be the ideal conditions of slow freezing to reduce this effect.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Comparison with other DNA strand break assays (TUNEL and COMET) has shown that the DNA denaturation measured in the SCSA is largely due to DNA strand breaks (Gorczyca et al 1993, Chohan et al 2004. The sperm samples in BWW were adjusted to a concentration of 1-2!10 6 cells/ml with TNE (0.15 M NaCl, 0.1 M Tris, 1 mM EDTA pH 7.4); 100 ml of this sample was mixed with 200 ml acid detergent solution (0.1% Triton X-100, 0.15 M NaCl, 0.08 M HCl).…”
Section: Sperm Chromatin Structure Assaymentioning
confidence: 99%